1999
DOI: 10.1679/aohc.62.165
|View full text |Cite
|
Sign up to set email alerts
|

Changes in c-Fos Expression Induced by Noxious Stimulation in the Trigeminal Spinal Nucleus Caudalis and C1 Spinal Neurons of Rats after Hyperbaric Exposure.

Abstract: The present study aims to test the hypothesis that hyperbaric exposure inhibits nociceptive processing in the trigeminal spinal nucleus caudalis and C1 spinal neurons. We investigated the c-Fos-like immunoreactivity of the brainstem and upper cervical spinal cord (C1 region) following an injection of mustard oil (15 microliters of 20%) into the nasal mucosa of pentobarbital anesthetized rats after exposure to hyperbaric (2-atmospheres, 1 h) and normobaric pressures. After the hyperbaric exposure, the mean numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Based on evidence that complete or partial relief from TMD occurred after receiving endodontic treatment or having tooth extraction, Wright and Gullickson (1996) suggested that acute pulpalgia acts as a significant factor in forming TMD symptoms. Because the C1 region is considered as an extension of the Vc, which receives most nociceptive inputs from the trigeminal nerve and because C1 spinal neurons that have somatic receptive fields in the facial skin are stimulated by electrical stimulation of the tooth pulp (TP) Takeda et al, 1999;Tanimoto et al, 2002), we hypothesized that C1 spinal neurons responding to TP stimulation are also excited by electrical stimulation of the TMJ region.…”
Section: Introductionmentioning
confidence: 99%
“…Based on evidence that complete or partial relief from TMD occurred after receiving endodontic treatment or having tooth extraction, Wright and Gullickson (1996) suggested that acute pulpalgia acts as a significant factor in forming TMD symptoms. Because the C1 region is considered as an extension of the Vc, which receives most nociceptive inputs from the trigeminal nerve and because C1 spinal neurons that have somatic receptive fields in the facial skin are stimulated by electrical stimulation of the tooth pulp (TP) Takeda et al, 1999;Tanimoto et al, 2002), we hypothesized that C1 spinal neurons responding to TP stimulation are also excited by electrical stimulation of the TMJ region.…”
Section: Introductionmentioning
confidence: 99%
“…Together, these findings indicate that resveratrol might attenuate chronic inflammatory pain in the clinical setting. Conversely, we previously showed, using an acute inflammation model, that a marker of neuronal activation, immediate early gene, Fos proto‐oncogene, AP‐1 transcription factor subunit ( c‐fos )‐like immunoreactivity of SpVc and C1–C2 spinal cord following injection of mustard oil (MO) into the nasal mucosa, was inhibited by hyperbaric exposure via the descending inhibitory control system . The chemical irritant of MO is an agonist of transient receptor potential ankyrin 1 (TRPA1) and has long been known to activate somatosensory neurons, resulting in acute pain and neurogenic inflammation .…”
mentioning
confidence: 99%
“…15,28 In another rat model, noxious stimulation of the nasal mucosa by mustard oil has been used to provoke c-Fos expression in the STN caudalis. 42 After exposure of the animals to hyperbaric conditions of 2 atmospheres for 1 hour the number in Fos-positive neurons was significantly lower compared with control conditions. It was discussed that this effect may have been central, possibly caused by an increased activity of descending inhibitory systems or facilitation of oxygen diffusion.…”
Section: Discussionmentioning
confidence: 60%
“…It was discussed that this effect may have been central, possibly caused by an increased activity of descending inhibitory systems or facilitation of oxygen diffusion. 42 Although inverse effects in the STN, that is, an increase in central nociceptive mechanisms, can principially not be excluded to occur under hypobaric conditions, the fact that in our experiments the neurons were differentially activated argues rather for a peripheral mechanism involved in the transmission of barometric pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation